Metode Ice Breaking dalam Meningkatkan Konsentrasi Mahasiswa pada Mata Kuliah Pengembangan Bahan Ajar - Alif Achadah; Siti Muawanatul Hasanah (Concept: Journal of Social Humanities and Education, 2024)
In the teaching and learning process in educational institutions, one should not be separated from a leader in the class and in this case the teacher or lecturer. The teacher as an educator in helping students in the learning process must pay attention to the methods used so that they can make the learning process interesting so that learning objectives can be achieved. The method used must also be able to bridge and overcome boredom and decreased concentration in students. So it is necessary for teachers to implement the ice breaking method as an alternative to overcome boredom and maintain students' concentration so that they remain stable in the learning process. This research aims to develop an ice breaking method in the aspect of increasing concentration in students. This research discusses (1) How does the implementation of the Ice Breaking method increase student concentration in the Development of Teaching Materials course for the PAI Study Program, Faculty of Islamic Sciences, Unira Malang?, (2) What are the results of applying the ice breaking method in increasing student concentration in the Development course? Teaching materials for the PAI study program, Faculty of Islamic Sciences, Unira Malang?